Transition metal complexes of tetracyclines - Cunningham, David Graham (Department of Chemistry, 2016)
Forty-one transition metals were studied to observe their complexing properties with the tetracyclines. Four metals were found to form sufficiently strong complexes with the tetracyclines to provide a basis for a rapid, reliable method of assaying the potency of the tetracycline products used in medicine today. Microbiological methods take twenty hours to perform; spectrophotometric methods may be completed within one hour. Twenty-eight of the transition metals showed evidence of complex formation with the tetracyclines; not all of these complexes were found to be suitable for the spectrophotometric assay of the tetracyclines, however. The ligand-metal ratios of some of the transition metal-tetracycline complexes were determined under specified conditions using Job's method. In the concentration range for ligand and metal (3 x 10⁻⁵ M), the 1 : 1 complexes appeared to predominate. Attempts were made to identify the binding sites of the metal ions on the tetracycline molecules, using infra-red spectrophotometry, but the results were inconclusive. The stability constant of one of the transition metal-tetracycline complexes was determined by a potentiometric method. Using this method, the result for the titanium-tetracycline complex was β₁= 3,4 x 10¹⁵ M⁻¹.